LEGAL REVIEW OF THE CONTRIBUTION OF FORENSIC MEDICINE ON LEGAL EVIDENCE - Okprianti, Reny; Emilson, Nur Husni; Tsabitah, Nabila; Fadiah, Nyayu Siti; Fadli, M. Bio; Saputra, M. Renaldy (JILPR Journal Indonesia Law and Policy Review, 2025)
The contribution of forensic medicine to the results of forensic examinations, such as autopsies, plays a crucial role in identifying key evidence and determining the cause of death. By adhering to professional ethics and standards, forensic doctors help uphold justice and the integrity of the legal system. The method used in this study is normative. This law enforcement is carried out in the form of valid evidence in the form of letters and statements according to experts. therefore the relationship between the two cannot be separated. Investigators, expert doctors, and other law enforcement officers work together to coordinate with each other so that each stage in proving a case produces results in the form of concrete evidence, so that it can be used as a consideration for decisions to be taken by judges in court. The role of forensic medical assistance is very necessary to find the material truth in murder cases in order to clarify the criminal case and obtain valid evidence, but the role of forensic medicine is not always successful, there are also obstacles that occur.